Describing Conceptual Content Based on Category Analysis: the case of the concept of philistinism - Papaurėlytė-Klovienė, Silvija (Respectus Philologicus, 2024)
The article discusses how different types of material can be used for concept content analysis. The analysis was based on the content associated with the category of philistinism and examples of conceptual metaphors of philistinism. The research conducted shows that this type of research material allows us to see a greater variety of features associated with the spoken concept and to reveal more nuances of the concept of philistinism associated with the worldview of the Lithuanian language. The analysis of the examples of verbalisation of the category of philistinism leads to the conclusion that this phenomenon of non-linguistic reality can be described as a combination of several mutually supporting features. The results of this analysis are complemented by a description of the actualisation of conceptual metaphors of philistinism in language. Significant features of the concept of philistinism are fear of change, emphasis on comfort and convenience, bad taste, lack of progress, stagnation and dormancy.